Enhanced Thermal Conductivity in a Diamine-Appended Metal-Organic Framework as a Result of Cooperative CO2 Adsorption - Babaei, Hasan; Lee, Jung-Hoon; Dods, Matthew N.; Wilmer, Christopher E.; Long, Jeffrey R. (American Chemical Society, 2020)
Diamine-appended variants of the metalorganic framework M-2(dobpdc) (M = Mg, Mn, Fe, Co, Zn; dobpdc(4-) = 4,4'-dioxidobiphenyl-3,3'-dicarboxylate) exhibit exceptional CO2 capture properties owing to a unique cooperative adsorption mechanism, and thus hold promise for use in the development of energy- and cost-efficient CO2 separations. Understanding the nature of thermal transport in these materials is essential for such practical applications, however, as temperature rises resulting from exothermic CO2 uptake could potentially offset the energy savings offered by such cooperative adsorbents. Here, molecular dynamics (MD) simulations are employed in investigating thermal transport in bare and e-2-appended Zn-2(dobpdc) (e-2 = N-ethylethylenediamine), both with and without CO2 as a guest. In the absence of CO2, the appended diamines function to enhance thermal conductivity in the ab-plane of e-2Zn(2)(dobpdc) relative to the bare framework, as a result of noncovalent interactions between adjacent diamines that provide additional heat transfer pathways across the pore channel. Upon introduction of CO2, the thermal conductivity along the pore channel (the c-axis) increases due to the cooperative formation of metal-bound ammonium carbamates, which serve to create additional heat transfer pathways. In contrast, the thermal conductivity of the bare framework remains unchanged in the presence of zinc-bound CO2 but decreases in the presence of additional adsorbed CO2.
Keywords: INITIO MOLECULAR-DYNAMICS; TOTAL-ENERGY CALCULATIONS; CARBON-DIOXIDE; FLUE-GAS; CAPTURE; TRANSPORT; METHANE; MOF-5; PART